2019
DOI: 10.1136/bmjopen-2018-025420
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills training for the radiotherapy team to manage cancer patients’ emotional concerns: a systematic review

Abstract: ObjectivesMany cancer patients experience high levels of anxiety and concern during radiotherapy, often with long-lasting effects on their well-being. This systematic review aims to describe and determine the effectiveness of communication skills training (CST) for the radiotherapy team (RT) to improve conversations in this setting and to support patients with emotional concerns.DesignSystematic review.InterventionsCST for RT members.Data sourcesOn 17 April 2018, databases Medline, Embase, Scopus and PsycNET w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The results of this study indicate that empathic communication can be developed both in doctors, nurses and support staff in hospitals. Other findings that are in line with the results of this study are stated by Van Beusekom et al who found that Communication Skill Training (CST) improves emotional conversations between radio therapy members and patients [47].…”
Section: Disscussionsupporting
confidence: 92%
“…The results of this study indicate that empathic communication can be developed both in doctors, nurses and support staff in hospitals. Other findings that are in line with the results of this study are stated by Van Beusekom et al who found that Communication Skill Training (CST) improves emotional conversations between radio therapy members and patients [47].…”
Section: Disscussionsupporting
confidence: 92%
“…Historically, HPs have had limited access to CST due to the delayed incorporation of CST into the medical curriculum, 10 expectations that some oncology disciplines, such as nursing, learn communication skills on the job, 11 limited availability of training, accessibility of face‐to‐face training, the time required and costs involved. Improvements in access to CST requires consideration of availability, delivery modality, scheduling which is amenable to busy HPs, and departmental support 12 . Face‐to‐face training is more expensive compared to web‐based training and requires a greater number of participants for education providers to recuperate costs 13 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the fact that more than a third of our surveyed population recommended to further emphasize non-technical skills in their education, such as communication and team training reflected the training needs from a professional perspective. In fact, the importance of these skills have been re-emphasized in the ESTRO core curricula and several small studies revealed that communicational workshop for professionals could improve not only self-efficacy but also patient satisfaction [ 16 18 ]. In view of these findings, it would be important to conduct surveys on this topic among a larger number of RO and RTT to confirm them.…”
Section: Discussionmentioning
confidence: 99%